Successful laparoscopic resection for cap polyposis: case report, literature review - Koichi Tamura; Kenji Matsuda; Shozo Yokoyama; Hiromitsu Iwamoto; Yuki Mizumoto; Yuki Nakamura; Daisuke Murakami; Hiroki Yamaue (Surgical Case Reports, 2018)
Abstract Background Cap polyposis is a rare gastrointestinal disease with endoscopically and pathologically distinctive features. Its exact etiology has not been fully elucidated. In a few cases, there was recurrence after inadequate treatment. Efficacy of Helicobacter pylori eradication therapy, however, has been shown in some published research. Case presentation A 70-year-old female patient developed intermittent mucous diarrhea with loss of body weight and visited a physician. Total colonoscopy showed multiple sessile polyps which were partially coadunated from the rectum to the sigmoid colon. Histopathological finding was tubular adenoma with mild atypia. The patient stayed for observation. Worsening symptoms following protein-losing enteropathy demanded surgical treatment because malignancy could not be ruled out. Laparoscopic resection was performed, and the surgical specimens revealed that the polypoid lesion mainly consisted of mild adenomatous glands which were covered with purulent granulation tissues. We made final diagnosis of cap polyposis and saw rapid improvement of her symptoms. Long-term observation is required after surgery. Conclusions We reported a case of successful laparoscopic resection of cap polyposis with protein-losing enteropathy (170 words).